Genetic diversity analysis and core germplasm construction of tea plants in Lu’an - Yan Wang; Huanyun Peng; Xiaoyan Tong; Xiaoyuan Ding; Cheng Song; Teng Ma; Haohao Wang; Wang Wei; Cunwu Chen; Junyan Zhu; Dong Liu (BMC Plant Biology)
Abstract Background Lu’an, as one of the two major tea-producing areas in Anhui Province, has a long history of tea planting and rich tea germplasm resources. However, the genetic diversity and population structure of local tea plants are still unclear. In order to better protect and utilize tea germplasm resources in Lu’an, 217 tea accessions from six geographical origins were used to assess genetic diversity of Lu’an tea plant germplasm through double digest restriction-site associated DNA sequencing (ddRAD-seq) technology. Results A total of 306,320 high quality single nucleotide polymorphism (SNP) markers were obtained. Population structure, phylogenetic relationships and principal component analysis (PCA) divided the entire population into three groups. The genetic diversity and population differentiation analysis showed that the mean observed heterozygosity (Ho) was 0.06 ∼ 0.17, average nucleotide diversity (Pi) was 0.13 ∼ 0.26, and pairwise fixation index (Fst) was 0.01 ∼ 0.15. In addition, a core tea germplasm set composed of 50 tea germplasm sets was established. Conclusion Our study demonstrated that the germplasm resources of the Lu’an tea plants exhibit significant genetic diversity. A core germplasm sets for the Lu’an tea plants has been established, which effectively represents the genetic diversity of the entire tea germplasm collection. This study provided the basis for genetic research, germplasm protection and breeding of tea plants in Lu’an.